Carbon Reduction Calculation and Application in the Life Cycle of Green Buildings Based on Building Information Modeling - Liao Yasha; Cheng Hua (E3S Web of Conferences)
Amidst the backdrop of global warming, many countries mandate the calculation of building carbon emissions during architectural design. This paper expounds the calculation methods for building carbon emissions from the perspective of the entire life cycle of a building. Utilizing BIM technology, it establishes the BIM-Based Green Building Life Cycle Carbon Emission Calculation and Carbon Reduction Analysis Model, which is used to calculate the carbon emissions across the entire life cycle of a building and to conduct comparative analyses of carbon reduction following scheme optimization. Finally, combined with Zunyi Culture and Art Center, the model was applied to calculate the carbon emissions of the project, and the green technology optimization scheme was adopted. The total carbon reduction after optimization was 3014553.01 kgCO2, and the carbon reduction per unit area was 421.07 kgCO2/m2. It provides ideas and references for enterprises to calculate building carbon emission.